PENGEMBANGAN DESAIN KOMPETENSI DAN TUJUAN PEMBELAJARAN UPAYA MENINGKATKAN EFEKTIVITAS PROSES PEMBELAJARAN PAI - Moh. Zahrur Riyadh; Muhammad Akmaludin; Luluk Mukarromah; Devy Habibi Muhammad (PT. Sulthan Journal Publisher, 2026)
This study discusses the development of competency design and learning objectives in improving the effectiveness of Islamic Religious Education (PAI) learning. The development of competency design is an important aspect in creating a systematic, directed, and student-centered learning process. In PAI learning, competency design and learning objectives are not only oriented toward mastering religious materials, but also toward shaping Islamic character, religious attitudes, and students’ worship practice skills. This study uses a literature review approach by examining various scientific sources related to competency design, learning objectives, and PAI learning. The results show that the integration of competency design and learning objectives can improve students’ participation, motivation, and understanding in the learning process. In addition, the use of technology and learning media supports the creation of more active, creative, and innovative PAI learning. However, its implementation still faces several obstacles, such as limited teacher competence and educational facilities. Therefore, collaboration between the government, schools, and teachers is needed to improve the quality of competency-based learning so that the goals of Islamic education can be achieved optimally. Keywords: competency design, learning objectives, learning effectiveness, Islamic Religious Education.